2019
DOI: 10.2196/10155
|View full text |Cite
|
Sign up to set email alerts
|

What Can Be Achieved With Motivation-Based Teaching of Medical Students? A Monocentric Retrospective Audit of Retention Among Highly Motivated Graduates Who Underwent the Learning-by-Doing Concept in Anesthesiology and Intensive Care Medicine

Abstract: Background Medical education, in general, is undergoing a significant shift from traditional methods. It becomes very difficult to discover effective teaching methods within the limited possibilities in patient hands-on education, especially as seen in anesthesiology and intensive care medicine (AIM) teaching. Motivation-based teaching is very popular in all other aspects of education, but it has received scant attention in medical education literature, even though it can make a real difference fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…SBL leverages interactive scenarios termed Virtual Scenarios (VSs) in general and Virtual Patients (VPs) in medical education, to mimic real-world problems, thereby enhancing student engagement (Woodham et al, 2017) and performance (Poulton et al, 2014). This more immersive approach, involving elements of simulation (Poulton et al, 2014) and serious games (Klincova et al, 2019), aligns with our investigation into the integration of innovative educational strategies with PBL and TBL. Notably, a systematic review following Cochrane methodology (Kononowicz et al, 2019) has demonstrated the effectiveness of these scenarios in improving clinical reasoning, procedural skills, and teamwork in health professions education, which are key aspects of our study's focus.…”
Section: Introductionmentioning
confidence: 54%
“…SBL leverages interactive scenarios termed Virtual Scenarios (VSs) in general and Virtual Patients (VPs) in medical education, to mimic real-world problems, thereby enhancing student engagement (Woodham et al, 2017) and performance (Poulton et al, 2014). This more immersive approach, involving elements of simulation (Poulton et al, 2014) and serious games (Klincova et al, 2019), aligns with our investigation into the integration of innovative educational strategies with PBL and TBL. Notably, a systematic review following Cochrane methodology (Kononowicz et al, 2019) has demonstrated the effectiveness of these scenarios in improving clinical reasoning, procedural skills, and teamwork in health professions education, which are key aspects of our study's focus.…”
Section: Introductionmentioning
confidence: 54%
“…These games may be used to prevent disease [ 3 ], improve the health of patients with disease [ 4 ], and enhance social interaction to improve health [ 5 ]. Additional genres of serious games teach medical professionals skills [ 6 - 8 ], ultimately attempting to improve patient outcomes by improving clinician knowledge. A central attraction of electronic serious games is their ability to educate, motivate, and involve users without using conventional patient education that relies heavily on less engaging and often more intense training, such as written instruction or one-on-one consultation.…”
Section: Introductionmentioning
confidence: 99%
“…These games may be used to prevent disease [3], improve the health of patients with disease [4], and enhance social interaction to improve health [5]. Additional genres of serious games teach medical professionals skills [6][7][8], ultimately attempting to improve patient outcomes by improving clinician knowledge. A central attraction of electronic serious games is their ability to educate, motivate, and involve users without using conventional patient education that relies heavily on less engaging and often more intense training, such as written instruction or one-on-one consultation.…”
Section: Introductionmentioning
confidence: 99%